Long term results of three anti-vascular endothelial growth factor agents in pachychoroid neovasculopathy - KAŞKAL, MERT (My University, 2022)
Purpose To assess morphological changes and visual results in eyes with pachychoroid neovasculopathy (PNV) that underwent different intravitreal anti-vascular endothelial growth factor (VEGF) agents. Materials and methods This is a retrospective, observational, comparative study that included 76 PNV eyes in 76 patients that were allocated to three groups according to the monotherapy injection procedure, as follows: the intravitreal bevacizumab (IVB) group, intravitreal ranibizumab (IVR) group, and intravitreal aflibercept (IVA) group. Central macular thickness (CMT), best-corrected visual acuity (BCVA), and subfoveal choroidal thickness (SFCT) were measured at baseline, after treatment 1st month, 3rd month, 6th month, and 12th month, and at the final post-treatment examination. Results Mean age of the patients was 57.31 +/- 5.91 years (range: 34-67 years). The mean duration of follow-up was 31.50 +/- 12.91 months (range: 13-60 months). The IVB group included 30 eyes, the IVR group included 22 eyes, and the IVA group included 24 eyes. There weren\"t any significant differences in BCVA changes between the groups at any post-baseline measurement time point. Although CMT did not change significantly in the IVB group from baseline to the final follow-up visit (baseline: 376.33 +/- 86.31 mu m; final visit: 340.80 +/- 122.70 mu m) (p = 0.172), CMT did change significantly in the IVA group (baseline: 383.41 +/- 131.83 mu m; final visit: 297.33 +/- 103.81 mu m) (p = 0.029) and IVR group (baseline: 379.18 +/- 97.93 mu m; final visit: 335.72 +/- 111.45 mu m) (p = 0.041). SFCT decreased significantly in the IVR and IVA groups (p = 0.015 and p < 0.001, respectively). The mean number of injections was 12.06 +/- 4.72 (range: 6-20) in the IVB group, 11.81 +/- 3.31(range: 7-17) in the IVR group, and 7.16 +/- 3.15 (range: 4-13) in the IVA group (p = 0.004). Conclusion All three anti-VEGFs were effective in terms of visual results in patients with PNV. Patients treated with IVA required fewer injections than those treated with IVB or IVR. Furthermore, IVR and IVA treatment significantly decreased SFCT, whereas IVB did not.
Keywords: Tıp; Sağlık Bilimleri; Cerrahi Tıp Bilimleri; Göz Hastalıkları ve Cerrahisi; Eczacılık; Meslek Bilimleri; Farmasötik Toksikoloji; Yaşam Bilimleri; Temel Bilimler; Medicine; Health Sciences; Surgery Medicine Sciences; Eye Diseases and Surgery; Pharmacology and Therapeutics; Professional Sciences; Pharmaceutical Toxicology; Life Sciences; Natural Sciences; GÖZ HASTALIKLARI; Klinik Tıp; Klinik Tıp (MED); TOKSİKOLOJİ; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); OPHTHALMOLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); TOXICOLOGY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Toksikoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Sağlık, Toksikoloji ve Mutajenez; Oftalmoloji; Optometri; Fizik Bilimleri; Toxicology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); Health, Toxicology and Mutagenesis; Ophthalmology; Optometry; Physical Sciences; Pachychoroid neovasculopathy; chronic central serous chorioretinopathy; subfoveal choroidal thickness; anti-vascular endothelial growth factor agents; SUBFOVEAL CHOROIDAL THICKNESS; COHERENCE TOMOGRAPHY ANGIOGRAPHY; AFLIBERCEPT; THERAPY; RANIBIZUMAB